Ali program Ekošola prispeva k odgovornejšemu ravnanju učencev tretjega triletja? - Potočnik, Katja; Golob, Nikolaja; Sikošek, Darinka (Revija za elementarno izobraževanje, 2010)
Does the Eco-school program contribute to a more responsible attitude of pupils in the last three years of primary school? Environmental education is obtained by raising the awareness of growing environmental problems and threats of the destruction to our planet Earth. They play an increasingly important role in the educational system both at the international level as well as in Slovenia. The central topic of this article focuses on exploring the responsible attitude of students attending eco-schools and students who attend schools that are not part of the Eco-school program. We surveyed their attitudes towards the environment and the students' environmental impact on their parents and families, respectively. The survey involved three primary schools in Slovenia. The results of the survey show that students have a good awareness of the environment and have, in most cases, a more responsible attitude regarding the environment. Mostly, students do not have an influence on their parents' attitude as regards the environment, stating that their parents show a responsible handling of the environment already. Also, according to the students' opinion, the family itself is the main factor in the development of their positive consciousness when it comes to the environment. Primary schools, regardless of whether they are eco-schools or not, encourage the development of a responsible, eco-friendly personality. Only with the long-term cooperation of parents can these goals be achieved.